Using Large-Scale Sensor Data to Test Factors Predictive of Perseverance in Home Movement Rehabilitation: Optimal Challenge and Steady Engagement - Ramos Muñoz, Edgar De Jesus; Swanson, Veronica Ann; Johnson, Christopher; Anderson, Raeda K.; Rabinowitz, Amanda R.; Zondervan, Daniel K.; Collier, George H.; Reinkensmeyer, David J. (Frontiers in Neurology, 2022)
Persevering with home rehabilitation exercise is a struggle for millions of people in the US each year. A key factor that may influence motivation to engage with rehabilitation exercise is the challenge level of the assigned exercises, but this hypothesis is currently supported only by subjective, self-report. Here, we studied the relationship between challenge level and perseverance using long-term, self-determined exercise patterns of a large number of individuals (N = 2,581) engaging in home rehabilitation with a sensor-based exercise system without formal supervision. FitMi is comprised of two puck-like sensors and a library of 40 gamified exercises for the hands, arms, trunk, and legs that are designed for people recovering from a stroke. We found that individuals maximally persevered in their amount of use of the system over a two-month period if they had 1) a moderate level of motor impairment and 2) high but not perfect success during the first week at completing the exercise game. Further, a steady usage pattern (versus accelerating or decelerating use) was associated with more overall exercise, and declines in exercise amount over time were associated with exponentially declining session initiation probability rather than decreasing amounts of exercise once a session was initiated. These findings confirm that an optimized challenge level and regular initiation of exercise sessions predict achievement of a greater amount of overall rehabilitation exercise and suggest how home rehabilitation programs and exercise technologies can be optimized to promote perseverance.